Pembalikan Oposisi Biner Cerita Si Kabayan Ditinggal Kawin Pada Film Di Youtube - Iwan Muhammad Ridwan; Yanti Heriyawati; Enok Wartika (Pascasarjana ISBI Bandung, 2022)
ABSTRACTThe figure of Si Kabayan has always been identified as a stupid, lazy but clever character who can always beat his rivals. However, his figure in a new genre film, namely a sketch film on youtube media, has a shift in character. Si Kabayan's bumpkin figure has been deconstructed into a Kabayan living in the city. Likewise, his stupidity has shifted into one who has religious values as the other side of the Si Kabayan character in the original story. Using Derrida's deconstruction analysis, it can be seen the symbols presented through the visual narration of the film entitled Si Kabayan Ditinggal Kawin published on Kampung Utan TV Youtube channel. The study was conducted through narrative and visual stories at the level of representational reality and ideology. The changes occuring in a number of visual narrative elements are seen as a form of rearranging the narrative of Si Kabayan's life in oral stories. Based on the results of the reading of the narrative in the film Kabayan Ditinggal Kawin, there is a reversal of the binary opposition hierarchy, namely; (1) reversal of the binary opposition hierarchy of smart and stupid, (2) reversal of the binary opposition hierarchy of men and women, (3) reversal of the binary opposition hierarchy of village and city.Keyword: si kabayan, binary opposition, filmABSTRAKSosok Si Kabayan selalu diidentikan dengan karakter pandir, pemalas namun cerdik yang sering kali bisa mengalahkan lawan-lawan dalam kehidupannya. Namun kemunculannya dalam film genre baru yakni film sketsa pada media baru youtube, sosok Si Kabayan telah mengalami pergeseran karakter dalam bentuk pembalikan oposisi biner. Sosok Si Kabayan yang udik telah didekonstruksi menjadi Kabayan yang tinggal di kota. Begitu juga dengan kepandirannya telah bergeser pada jiwa yang mimiliki nilai religius sebagai sisi lain dari tokoh Si Kabayan dalam cerita asalnya. Melalui analisis dekonstruksi Derrida nampak simbol-simbol yang dihadirkan melalui narasi visual dari film yang berjudul Si Kabayan Ditinggal Kawin pada channel youtube Kampung Utan TV. Kajian dilakukan melalui naratif cerita dan visual pada level reality representasional dan ideology. Perubahan-perubahan yang terjadi dalam sejumlah unsur naratif visual terlihat sebagai bentuk penyusunan ulang dari narasi kehidupan Si Kabayan dalam cerita-cerita lisan. Berdasarkan hasil pembacaan terhadap narasi dalam film Kabayan ditinggal kawin, terdapat pembalikan hierarki oposisi biner yakni; (1) pembalikan hierarki oposisi biner pintar bodoh, (2) pembalikan hierarki oposisi biner laki-laki perempuan, (3) pembalikan hierarki oposisi biner kampung kota.Kata kunci: si kabayan, oposisi biner, film